2009
DOI: 10.1111/j.1442-200x.2009.02856.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced oxygen protocol decreases the incidence of threshold retinopathy of prematurity in infants of <33 weeks gestation

Abstract: A significant decrease in the rate of threshold ROP in infants of <33 weeks gestation was observed after implementation of the new clinical O(2) management practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 6 publications
0
19
3
2
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18] The authors of multiple reports [19][20][21][22][23][24][25] have demonstrated a marked increase in both the incidence and severity of ROP in humans and related neovascular retinopathies in other mammals after oxygen supplementation. Aggressive supplemental oxygenation of premature infants also strains the health care system both in the extended duration of therapy as well as more intensive outpatient care not necessary for infants with a more moderate oxygen saturation target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16][17][18] The authors of multiple reports [19][20][21][22][23][24][25] have demonstrated a marked increase in both the incidence and severity of ROP in humans and related neovascular retinopathies in other mammals after oxygen supplementation. Aggressive supplemental oxygenation of premature infants also strains the health care system both in the extended duration of therapy as well as more intensive outpatient care not necessary for infants with a more moderate oxygen saturation target.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive supplemental oxygenation of premature infants also strains the health care system both in the extended duration of therapy as well as more intensive outpatient care not necessary for infants with a more moderate oxygen saturation target. 10,26 However, although lower levels of oxygen supplementation do result in a lower incidence of ROP and related neovascular retinopathies in other mammals, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] overaggressive limitation of oxygen to less physiologic levels may increase morbidity and mortality, 18,27,28 although a more physiologic reduction could be less detrimental. 29 In this study we compared the incidence and severity of ROP during the 2 years immediately before and the 2 years immediately after the initiation of a new oxygen protocol targeting oxygen saturations at 85% to 93% for all inborn premature infants at a level III neonatal intensive care unit (NICU).…”
Section: Discussionmentioning
confidence: 99%
“…Three randomized trials [16,22,23] and 5 observational studies [12,20,24,25,28] including 4,612 patients investigated the association between SpO 2 and BPD ( table 2 ). There was a significantly reduced incidence of BPD or lung problems in the low versus high saturation groups.…”
Section: Resultsmentioning
confidence: 99%
“…One randomized trial [16] and 7 observational studies [12,20,[24][25][26][27][28] including 3,811 patients investigated the association between SpO 2 and the incidence of severe ROP ( table 2 ). There was a significantly reduced incidence of severe ROP in the low SpO 2 group with a summary RR of 0.42 (95% CI 0.34-0.51) ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation